SPIONs for cell labelling and tracking using MRI: magnetite or maghemite?. (30th November 2017) - Barrow, Michael; Taylor, Arthur; Fuentes-Caparrós, Ana M.; Sharkey, Jack; Daniels, Luke M.; Mandal, Pranab; Park, B. Kevin; Murray, Patricia; Rosseinsky, Matthew J.; Adams, Dave J.
Abstract : SPIONs consisting predominantly of magnetite or maghemite display distinct chemical stability in solution but equivalent imaging properties when in cells. Abstract : Although there is extensive literature covering the biomedical applications of superparamagnetic iron oxide nanoparticles (SPIONs), the phase of the iron oxide core used is not often taken into account when cell labelling and tracking studies for regenerative medicine are considered. Here, we use a co-precipitation reaction to synthesise particles of both magnetite- (Fe3 O4 ) and maghemite- (γ-Fe2 O3 ) based cores and consider whether the extra synthesis step to make maghemite based particles is advantageous for cell tracking.